Anchoring Sweden's Post-conscript Military: Insights From Elites in the Political and Military Realm. Issue 3 (July 2019) - Wallenius, Claes; Brandow, Carina; Berglund, Anna Karin; Jonsson, Emma
The universal nature of conscription ties or anchors broad segments of society to the military. What happens to societal anchoring after the draft ends? Using in-depth interviews with two groups of elites, this article explores factors that promote and hinder the Swedish Military's societal anchoring post-conscription. The first group consisted of 18 executives at the Swedish Armed Forces (SAF) headquarters with strategic positions in relation to societal anchoring. The second group consisted of 15 representatives from the corresponding political level: members of the parliamentary Committee on Defense and their officials. The interviews were semistructured and analyzed according to a grounded theory-inspired approach. Main themes concerning obstacles were the public's low interest and dated knowledge, an unclear political debate resulting in vague expectations concerning the SAF, as well as unclear responsibility for informing the public, and confidence gaps between the military and the political elite.